A postmortem study of length and internal diameter of the cystic duct (Journal of Dhaka National Medical College & Hospital, 2013)
The cystic duct arises from the neck of the gallbladder and ends by joining with the common hepatic duct to form the common bile duct. Gallstones are frequently squeezed into the cystic duct and leads to spasm of the duct wall producing severe biliary colic. So, length and internal diameter of the cystic duct is very important for the surgeon for better management. This is an observational, descriptive type of study which was carried out in the Department of Anatomy, Sir Salimullah Medical College, Dhaka from July 2010 to June 2011. The number of sample was 62 postmortem human gallbladder with cystic duct which were collected from unclaimed dead bodies of the morgue of Dhaka Medical College and Sir Salimullah Medical College. The samples were divided into three different age groups. i.e. group A (10-20 yrs), group B (21-40 yrs) and group C (41-70 yrs). Morphological study was carried out on all samples by fine dissecting method. Statistically significant difference were found when values were compared between different age groups except the internal diameter of the cystic duct when group B was compared with group C, the result was found not significant (P>0.05). There was change in length and internal diameter of the cystic duct in relation to age.J. Dhaka National Med. Coll. Hos. 2013; 19 (01): 35-38